Civic and political participation of young immigrants and Portuguese - Ribeiro, Norberto (2016)
This article contributes to the discussion of the factors that can promote or hinder civic and political participation of young people of Portuguese and immigrant origin. Survey data (N=1010) of youngsters of Angolan, Brazilian, and Portuguese origin (15-29 years old) were analyzed, exploring the differences in origin group, gender and number of books at home (i. e., cultural capital) regarding their effects on the motivations and barriers to participate, and on the conceptions of citizenship. The results indicate that high levels of cultural capital can overcome ethnic disadvantages.